2009
DOI: 10.1021/la901071v
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Protein Carriers for Modulating DNA Release

Abstract: Aqueous mixtures of oppositely charged polyelectrolytes undergo associative phase separation, resulting in coacervation, gelation, or precipitation. This phenomenon has been exploited in forming DNA gel particles by interfacial diffusion. We report here the formation of DNA gel particles by mixing solutions of double-stranded DNA with aqueous solutions containing two cationic proteins, lysozyme and protamine sulfate. The effect of the lysozyme/ protamine ratio on the degree of DNA entrapment, surface morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…Studies of DNA release from protein-DNA particles formed by the dropwise addition method have demonstrated that these particles can present DNA release profiles of up to 1,000 h, confirming the stability of these protein-DNA gel particles [63]. In the present study, the stability of these particles in the culture medium was also confirmed.…”
Section: Cytotoxicitysupporting
confidence: 83%
See 2 more Smart Citations
“…Studies of DNA release from protein-DNA particles formed by the dropwise addition method have demonstrated that these particles can present DNA release profiles of up to 1,000 h, confirming the stability of these protein-DNA gel particles [63]. In the present study, the stability of these particles in the culture medium was also confirmed.…”
Section: Cytotoxicitysupporting
confidence: 83%
“…The development of biodegradable, biocompatible DNA gel particles has been achieved using natural proteins or mixtures of proteins [52,[63][64] Lysozyme is one of…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Each one of the release stages was related to a specific value of n and k, suggesting that the overall release profile of Vit-B 12 from the protein-based microparticles is predicted by different types of mechanisms and release rates. These two step-release mechanisms have been found for release of DNA [41] and BSA and FITC-dextran [42] from DNA-based gels. Table 2 summarizes the data of n and k and other adjusting parameters for the two stages, where subscripts 1 and 2 represent the first and second stage, respectively.…”
Section: Vit-b 12 Release From the Microparticlesmentioning
confidence: 77%
“…A c c e p t e d M a n u s c r i p t Previous work in our lab has demonstrated the potential application of these protein-DNA gel 340 particles in the controlled encapsulation and release of DNA (Morán et al, 2009a). The magnitude 341 of the DNA release was controlled and controlled release systems were achieved by changing the 342 LS/PS ratio in the protein solution where particles were formed.…”
Section: [Fig 2 Here]mentioning
confidence: 99%